A New Parametric Differential Operator of p-Valently Analytic Functions. (31st October 2021) - Hadid, Samir B.; Ibrahim, Rabha W.; Murugusundaramoorthy, G.
Abstract : Newly, numerous investigations are considered utilizing the idea of parametric operators (integral and differential). The objective of this effort is to formulate a new 2D-parameter differential operator (PDO) of a class of multivalent functions in the open unit disk. Consequently, we formulate the suggested operator in some interesting classes of analytic functions to study its geometric properties. The recognized class contains some recent works.